Standardizing bimanual vaginal examination using cognitive task analysis. - Plumptre,I; Mulki,O; Granados,A; Gayle,C; Ahmed,S; Low-Beer,N; Higham,J; Bello,F (International Journal of Gynecology & Obstetrics, 2017)
OBJECTIVE: To create a standardized universal list of procedural steps for bimanual vaginal examination (BVE) for teaching, assessment, and simulator development. METHODS: This observational study, conducted from June-July 2012 and July-December 2014, collected video data of 10 expert clinicians performing BVE in a nonclinical environment. Video data were analyzed to produce a cognitive task analysis (CTA) of the examination steps performed. The CTA was further refined through structured interviews to make it suitable for teaching or assessment. It was validated through its use as a procedural examination checklist to rate expert clinician performance. RESULTS: BVE was deconstructed into 88 detailed steps outlining the complete examination process. These initial 88 steps were reduced to 35 by focusing on the unseen internal examination, then further refined through interviews with five experts into 30 essential procedural steps, five of which are additional steps if pathology is suspected. Using the CTA as a procedural checklist, the mean number of steps performed and/or verbalized was 21.6 ± 3.12 (72% ± 10.4%; range, 15.9-27.9, 53%-93%). CONCLUSION: This approach identified 30 essential steps for performing BVE, producing a new technique and standardized tool for teaching, assessment, and simulator development.